2016
DOI: 10.1161/circulationaha.116.021831
|View full text |Cite
|
Sign up to set email alerts
|

Management of Bleeding With Non–Vitamin K Antagonist Oral Anticoagulants in the Era of Specific Reversal Agents

Abstract: Vitamin K antagonists are commonly used by clinicians to provide anticoagulation to patients who have or are at risk of having thrombotic events. In addition to familiarity with the dosing and monitoring of vitamin K antagonists, clinicians are accustomed to using vitamin K if there is a need to reverse the anticoagulant effect of vitamin K antagonists. There are now 4 new non-vitamin K antagonist oral anticoagulants (NOACs) that are attractive alternatives to vitamin K antagonists. Despite similar or lower ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
79
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 83 publications
0
79
0
3
Order By: Relevance
“…Guidelines and institutional protocols will need to be developed to ensure the appropriate use of reversal agents only for patients with serious or life-threatening bleeding, which may include bleeding causing hemodynamic compromise, intracranial hemorrhage, bleeding into a critical organ or closed space, persistent bleeding despite general supportive measures and local hemostatic support, and/or risk of recurrent bleeding due to excess NOAC drug exposure due to delayed clearance of NOAC (eg, acute renal failure) or overdose. 1 Specific reversal agents are preferred, if available, over non-specific hemostatic agents, as the latter are less effective in reversing coagulation abnormalities, have not been shown to improve outcomes, and are potentially prothrombotic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guidelines and institutional protocols will need to be developed to ensure the appropriate use of reversal agents only for patients with serious or life-threatening bleeding, which may include bleeding causing hemodynamic compromise, intracranial hemorrhage, bleeding into a critical organ or closed space, persistent bleeding despite general supportive measures and local hemostatic support, and/or risk of recurrent bleeding due to excess NOAC drug exposure due to delayed clearance of NOAC (eg, acute renal failure) or overdose. 1 Specific reversal agents are preferred, if available, over non-specific hemostatic agents, as the latter are less effective in reversing coagulation abnormalities, have not been shown to improve outcomes, and are potentially prothrombotic.…”
Section: Discussionmentioning
confidence: 99%
“…These agents have several distinct advantages in comparison with warfarin, including rapid onset and offset of action, absence of an effect of dietary vitamin K intake on their activity, fewer drug interactions, and the ability to be given in fixed doses without routine coagulation monitoring due to their predictable pharmacokinetic and pharmacodynamic effects. 1 Large phase III trials in patients with AF as well as venous thromboembolism have demonstrated that NOACs have a favorable riskbenefit profile compared with that of warfarin. They are as effective, if not more effective, than warfarin in preventing thromboembolism, and are far safer with respect to serious bleeding, particularly with regard to the risk of intracranial hemorrhage, which is decreased by > 50%.…”
Section: Introductionmentioning
confidence: 99%
“…Nonspecific hemostatic agents such as recombinant factor VII, factor VIII inhibitor bypassing activity, or PCCs have been suggested based on clinical need. [321][322][323] A dabigatran-directed neutralizing antibody, idarucizumab, has been approved for use. A prospective study showed that idarucizumab normalized the elevated ECT in 88% to 98% of patients, an effect that was seen within minutes.…”
Section: Dabigatranmentioning
confidence: 99%
“…Currently, a registered antidote against new direct inhibitors of anticoagulation is available only for dabi gatran, but there are ongoing advanced studies related to obtaining clinical confirmation of the possibility of using an antidote for drugs from the group of factor Xa inhibitors, e.g. adnexanet alpha [38][39][40]. While waiting for the results of this studies, it is worth noting that despite the fact that the availability of antidotes seems to be, by all means, justified, according to the earlier observations in most cases bleeding complications reported during the use of new anticoagulant molecules most likely do not require the use of a specific antidote [22,36,39].…”
mentioning
confidence: 99%
“…adnexanet alpha [38][39][40]. While waiting for the results of this studies, it is worth noting that despite the fact that the availability of antidotes seems to be, by all means, justified, according to the earlier observations in most cases bleeding complications reported during the use of new anticoagulant molecules most likely do not require the use of a specific antidote [22,36,39]. The above-mentioned observations were mostly made on the basis of the pharmacological properties of new oral anticoagulants and, above all, their relatively short time of action [6][7][8][9][10].…”
mentioning
confidence: 99%